Optimization of Technology of Canned Meat Products - Bal’-Prylypko, L.; Slobodianiuk, N.; Brona, G.; Moroziuk, R.; Al’ Ravashdekh, A. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
It was determined the parameters of quality of functional canned mince meat productsoptimized by adding of preparations of proteins of blood plasma (2%) and cellular tissues (2.5%), and developed the optimized technology of their production.
Keywords: canned mince meat products; technology; protein; consistency; nutritional value; juiciness; viscosity; and holding of water; nutritional fibers